INFLUENCE OF STRATEGIC LEADERSHIP INITIATIVES ON WORKPLACE HARMONY IN THE NAKURU COUNTY GOVERNMENT - SUMUKWO, ZACHARY K. (KABARAK UNIVERSITY, 2016)
With the advent of devolution in Kenya, it is possible that most of the conflict in the public sector organizations today stem from the restructuring of government. Many County governments are yet to resolve some teething problems on many fronts which threaten to impede their functions and slow down the devolution process considerably. Some of these problems can be resolved through strategic leadership. However, studies on strategic leadership and organizational behavior have not linked strategic leadership to conflict management in the workplace. Therefore, the general objective of the study was to investigate influence of strategic leadership initiatives on workplace harmony in Nakuru County Government. Its specific objectives were to determine the influence of dialogue facilitation, equitable resource allocation, negotiation and employee bonding as strategic leadership initiatives on workplace harmony in the Nakuru County Government. The study was guided by the the Deprivation Theory and the Strategic Choice Theory. Survey research design was adopted for the study targeting the management and staff of the Nakuru County Government. A sample size of 98 respondents obtained using stratified random sampling was used. Self-administered questionnaires were used as data collecting instruments. Data was analyzed using descriptive statistics (mainly frequencies, percentages and Chi-squares) and inferential statistics, mainly Pearson product moment correlation and multiple linear regression analysis. The findings revealed that through strategic leadership, dialogue was used in the organization to complement other forms of diplomatic or political processes, or lay the groundwork for future and more formal talks, and not replace them. The study also found that through strategic leadership members of the organization sought to create common goals and hence bonds within the members of the organization. It was recommended that the organization carry out onboarding practices to ensure that new employees or employees being moved to other areas are conversant with the communications channels to be used when airing their views. There is also need for the organization’s management to ensure that a committee has been put in place that ensures equitable distribution of resources. It is also recommended that the organization management focus their strategic leadership skills on negotiating industrial disputes. The organization’s strategic plan on promotion also ought to be well canvassed and circulated among the members so as to enable them see the organization’s vision for leadership in the areas concerned.
FULL TEXT
Keywords: conflict management, strategic leadership, workplace conflict resolution